Immigration law enforcement, social support, and health for Latino immigrant families in Southeastern Michigan - Benavides, Quetzabel; Doshi, Monika; Valentín-Cortés, Mislael; Militzer, Maria; Quiñones, Spring; Kraut, Ruth; Rion, Raymond; Bryce, Richard; Lopez, William D.; Fleming, Paul J. (Social science & medicine (1982), 2021)
Social support is a key determinant of physical and mental health outcomes. Implementation of restrictive immigration policies in the U.S. under the Trump administration impacted the way mixed-status Latino families (i.e., those with varying legal statuses, including undocumented) maintained social relationships and provided social support. This paper examines how federal immigration policies introduced after the 2016 U.S. presidential election impacted social networks and support related to health for undocumented and mixed-status Latino families. We interviewed 23 clients and 28 service providers at two Federally Qualified Health Centers and one non-profit organization in Southeast Michigan. The interviews were audio-recorded, transcribed, and analyzed thematically. Policies introduced during the Trump administration increased opportunities for deportation and contributed to the isolation of mixed-status Latino families by transforming safe spaces of social interaction into prime locations for immigration enforcement activity. Despite the limitations created by these restrictive policies, mixed-status families employed alternative mechanisms to maintain access to vital informal and formal support systems while simultaneously navigating emerging immigration-related threats. Elections have health consequences and immigration policies are needed that promote the health and well-being of Latino immigrant communities. •Introduction of “zero-tolerance” policies are fragmenting Latino social networks.•Mixed-status Latino families experienced increased isolation after 2016 elections.•Increased fear of deportation and separation impacted Latino mental health.•Mixed-status Latino families are mobilizing and responding to emerging needs.•Service providers are a source of social support for mixed-status Latino Families.